Making sense of regime complexity : exploring the applicability of cognitivist-rationalist integration - Chan, Samuel YingXu (Nanyang Technological University, 2021)
This study attempts to make sense of refugee regime complexity by applying a synthesis of theories. Echoing regime theory scholars, this study puts that a cognitivist-rationalist division of labour would avoid explanations that pit particular theories against each other, and provides fuller explanations of international regime complexes. This study takes refugee protection as the topic of concern, utilising Southeast Asia’s refugeerelating regime complex to illustrate its model. It represents a contribution to wider theoretical debates on regime complexities and is an attempt at 1) outlining a heuristic framework for understanding regime/regime complex changes, and 2) revealing opportunities for further research in the field of regime complexities.